The Discourse of Fani s’ Poetry in the light of Perspective of Norman Fairclough’s Critical Analysis (Raparin Journal of Humanities (RJH), 2026)
Discourse is the characteristic of the actions performed by the speaker in a social environment to convey a meaning that is incorrect and is the way of using language in the literary context Mortal poetry from the perspective of Norman Fairclough is an attempt to analyze the discourse of Fani poems.Fani, is one of the prominent poets of the mid-twentieth century in Bitwin and Pishdar, has become a prominent voice of his time. In this research, based on the contextual content of the texts and the historical aspects and from the perspective of the views of Norman Fairclough, we have tried to understand the political discourse. As a result, we have come to the conclusion that Fani has unconsciously tried to deal with language and use it in the service of literary expression and literary discourse, thus making poetry a political, social and national issue for Fani.The structure of our research consists of two parts: the first part is to introduce the terms and concepts of discourse, the steps of discourse analysis between the views of Norman and Fairclough, and the second part is to practice the poet's poems in discourse analysis, which is the interpretation of the content of the text using the historical and social dimensions, the analysis of political, national and social discourse in Fani's poems. The list of references and abstract of the study are discussed in Arabic and English.